The psychosocial functioning in adolescents with severe obesity evaluated throughout the strengths and difficulties questionnaire (SDQ): a preliminary report - Guerrini Usubini, Anna; Bottacchi, Michela; Morelli, Giovanna; Caroli, Diana; Marazzi, Nicoletta; Castelnuovo, Gianluca; Sartorio, Alessandro (Frontiers in Psychology, 2024)
Introduction Childhood obesity is associated with poor psychological adjustment. Severely impacts the psychological adjustment of young patients. To assess the psychological functioning of children and adolescents, several questionnaires have been proposed so far. Although the Strengths and Difficulties Questionnaire (SDQ) is one of the most well-used tools, its application in obesity research is scarce. The study is aimed at assessing the psychological profile of a sample of Italian children and adolescents seeking an in-hospital multidisciplinary body weight reduction program for obesity, via SDQ. Methods One hundred and fourteen consecutive Italian children and adolescents with obesity (43 males/71 females, age range: 11–17 years, mean age ± SD: 15.1 ± 1.66, body mass index-BMI ± SD: 37.4 ± 6.13 kg/m2), were recruited at the Division of Auxology, Istituto Auxologico Italiano IRCCS, Piancavallo (VB). Results Obese Females reported worse conditions of emotional symptoms (t = 5.48; p < 0.001) and peer problems (t = 2.34; p = 0.021), as well as higher which were associated with greater scores of pro-social behaviors than obese males (t = 3.07; p = 0.003). The total difficulties score (t = 4.00; p < 0.001) and the total impact score (t = 4.53; p < 0.001) were significantly higher in females than males. No statistically significant differences in SDQ variables were found in relation to the degree of obesity (BMI SDS: 2–2.99; BMI SDS: > 3). Discussion These findings can contribute to understand the psychological condition of adolescents with obesity in a better way and also to develop effective interventions for the treatment of pediatric obesity which not only take into account the medical and physical aspects but also the emotional and social difficulties expressed by adolescents with obesity.